THE EUROPEAN UNION, INDONESIA, AND THE RENEWABLE ENERGY DIRECTIVE - Rosario J Taa; Karinda Febrinia; Jhon Jefri Rumbino; Yoel Parakletos Pandiangan; Renata Iglesyanna; Christy Melvadera Sitompul (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2020)
This research tries to explain how to overcome the problems that occur in the EU (European Union). The concept used is environmental diplomacy. The concept of environmental diplomacy is used to explain the environmental conflict between the EU and Indonesia. Keywords: EU Clean Energy, Diplomacy, Environment.